Medication rationality in treating depression - KAVALIAUSKIENĖ, Liubov; PEČIŪRA, Rimantas; ADOMAITIENĖ, Virginija (Acta medica Lituanica, 2011)
Background. The costs of depression treatment in Lithuania increase because of high depression relapse rates which indicate the necessity to evaluate first-time depression treatment rationality. The aim of this study was to evaluate the use of antidepressants according to the opinion of three groups of specialists (family doctors, psychiatrists and pharmacists) in order to assess the possibilities of a more rational use of depression treatment costs rationalizing opportunities. Materials and methods. Data on depression diagnoses were obtained from the Republic Psychiatric Health Centre. In 2009, 361 Lithuanian pharmacist, 317 family doctors and 280 psychiatrists were interviewed. The data were processed using the Statistical Package for the Social Sciences program. Results. In the study period (2004–2009), the volume of total depression diagnoses grew up by 12% and the number of relapsed depression diagnoses by 27%. Among family doctors, 13% still don’t launch depression treatment by themselves, and 62% of them refer patients to psychiatrists in cases of depression relapse. Those who prescribe a medicine all alone in most cases use sertraline, but even 38% of family doctors mention benzodiazepines. According to family doctors’ answers, 32% of them reevaluate the effect of medications in 4 weeks and 25% do not monitor it at all. More than 50% of pharmacists have noted that every day they are asked by patients for antidepressants without prescription. Conclusions. The abundance of cases of recurrent depression, recorded by family doctors, encourage to revise the preparedness of family doctors to treat this disease. The specialists’ opinion makes us to reevaluate and question the quality of depression treatment and to rationalize the efficiency of depression treatment in Lithuania as regards its both economic and social aspects. Keywords: depression treatment, antidepressants, depression relapse